Problems and prospects in the utilization of animal traction in semi-arid West Africa: Evidence from Niger - Williams, Timothy O. (Elsevier, 1997)
The use of animal draft power for soil tillage has long been a major theme of agricultural development programmes in semi-arid West Africa. The rationale for animal traction utilization ranges from increasing agricultural productivity and income to relieving the drudgery in farm work. Yet, its adoption remains low and localized. Previous research has identified the conditions which favour the adoption of animal traction, but evidence on the potential benefits realizable from its use is mixed. The issue of how to improve the adoption and profitable utilization of animal traction in semi-arid West Africa remains an important topic given that mechanization of agriculture is inevitable. This paper uses data collected from villages in two different agroclimatic zones of Niger to demonstrate the regional variability of potential gains from animal traction. Production functions were estimated to determine the impact of animal traction use on area cultivated, labour input and aggregate yield. Multi-year partial budget streams were also estimated to evaluate the profitability of animal traction at each location. The results show that the use of animal traction did not have any significant impact on area cultivated, but increased the yields of sorghum (Sorghum bicolor (L.) Moench) and maize (Zea mays L.) by 12-15%. It increased labour input by 15 man-h ha-1 (man hours per hectare) in the dry agroclimatic zone, but reduced it by 50 man-h ha-1 in the wet zone. Rates of return on animal traction investment ranged from -4 to 18% in the dry zone and from 14 to 58% in the wet zone. These results suggest that the impact of animal traction on agricultural production varies by region and depends on a broad set of agroecological and economic conditions. The absence of these conditions in marginal areas strictly limits potential utilization and profitability. On efficiency grounds, it is recommended that animal traction should be promoted only in areas where the climate, soil and economic conditions permit its intensive and profitable utilization.